The Risk Factors and Pregnancy Outcomes of 48 Cases of Heterotopic Pregnancy from a Single Center - Jeon, Ji Hyun (J Korean Med Sci, 2016)
The purpose of this study was to investigate risk factors that are associated with heterotopic pregnancy (HP) following in vitro fertilization (IVF)-embryo transfer (ET) and to demonstrate the outcomes of HP after the surgical treatment of ectopic pregnancies. Forty-eight patients from a single center, who were diagnosed with HP between 1998 and 2012 were included. All of the patients had received infertility treatments, such as Clomid with timed coitus (n = 1, 2.1%), superovulation with intrauterine insemination (n = 7, 14.6%), fresh non-donor IVF-ET (n = 33, 68.8%), and frozen-thawed cycles (n = 7, 14.6%). Eighty-four additional patients were randomly selected as controls from the IVF registry database. HP was diagnosed at 7.5 ± 1.2 weeks (range 5.4-10.3) gestational age. In six cases (12.5%), the diagnosis was made three weeks after the patients underwent treatment for abortion. There were significant differences in the history of ectopic pregnancy (22.5% vs. 3.6%, P = 0.002). There were no significant differences in either group between the rates of first trimester intrauterine fetal loss (15.0% vs. 13.1%) or live birth (80.0% vs. 84.1%) after the surgical treatment for ectopic pregnancy. The risk factors for HP include a history of ectopic pregnancy (OR 7.191 [1.591-32.513], P = 0.010), abortion (OR 3.948 [1.574-9.902], P = 0.003), and ovarian hyperstimulation syndrome (OHSS) (OR 10.773 [2.415-48.060], P = 0.002). In patients undergoing IVF-ET, history of ectopic pregnancy, abortion, and OHSS may be risk factors for HP as compared to the control group of other IVF patients. The surgical treatment of HP does not appear to affect the rates of first trimester fetal loss or live birth.